Inorganic nano-carriers based smart drug delivery systems for tumor therapy - Zhaoqing Shi; Yun Zhou; Taojian Fan; Yaoxin Lin; Han Zhang; Lin Mei (Smart Materials in Medicine, 2020)
Tumor is a severe disease that affects human health. In addition to surgical treatment and radiotherapy, applying therapeutic agents that can kill the tumor directly or regulate immune systems is one of the most common treatments. The current problems of these therapeutic agents are lacking selective targeting of tumor and causing unfavorable side effects. In order to solve the problems and develop more effective medicines, nano-carriers are employed to fabricate smart drug delivery systems. In recent years, novel inorganic nano-materials, like mesoporous silica nanoparticles, gold nanoparticles, graphene oxide and black phosphorus, have shown talent in drug loading capacity, stability, and biocompatibility, which are becoming candidates for novel nano-carriers. This review not only provides a comprehensive summary on the mechanisms of inorganic nano-carrier based smart drug delivery systems but also summarizes their synthesis, applications, challenges and future possibilities.